ONLINE LEARNING FOR ISLAMIC EDUCATION IN THE INSAN MADANI INTEGRATED ISLAMIC JUNIOR SECONDARY SCHOOL 8 TANGERANG SELATAN DURING THE COVID-19 PANDEMIC: A CASE STUDY - Rusjdy Sjakyakirti Arifin; Nazela Salsabila Wihda (Kwangsan: Jurnal Teknologi Pendidikan, 2022)
The objective of this research was to analyze the impact of implementing online learning from home during the Covid-19 pandemic, especially for Islamic Education subject matter. The research was conducted at SMP Islam Terpadu Insan Madani 8 Jurangmangu, Tangerang Selatan-Banten, one of the Islamic Junior Secondary Schools at Jurangmangu, Tangerang Selatan, Banten. The research was conducted in a qualitative approach with data collection techniques through interviews, observation, and documentation. The study indicated that the online-based learning during the Covid-19 pandemic was carried out quite well following the government circular letters No. 4/2020 and No.15 of 2020. Some obstacles faced are unstable internet signals and limited facilities. Some examples of the obstacles were (1) the use of one smartphone for online learning in a family, so they had to take turns with siblings at home, (2) teachers had difficulty in providing practical learning materials, and (3) some parents had difficulties in operating gadgets and explaining the Islamic Education materials to their children. Some solutions in overcoming these obstacles were (1) to make changes to the online learning platform so that easier for parents to facilitate their children to learn from home, and (2) to provide internet credit subsidies by providing tuition waivers by 33%.